PENYELESAIAN SENGKETA HUTANG PIUTANG DI KALANGAN MASYARAKAT TALOHEN HULU KELURAHAN AMPAH KOTA KABUPATEN BARITO TIMUR - Syarifuddin, Syarifuddin; Dakhoir, Ahmad; Azizah, Sri Dewi Nur (AL-QARDH, 2016)
Debt is one of the activities muamalah are allowed in Islam. Most people choose the wrong place when the event of default of borrowing and cause disputes often occur crime and immoral actions against the borrower. Unlike the case with accounts payable disputes that occur in society Talohen Hulu. The purpose of this study was to determine the background of the debts, the form of contract debts and settlement of disputes when the event of default (wanprestasi)in among community of Talohen Hulu village of Ampah City district of East Barito.Â This study uses field research, the method used is descriptive qualitative approach. This research was conducted by collecting data that is direct observation, interviews, and gathering important documents. In addition it also examines Islamic books relating to debts that have been exacerbated by the arguments of the Quran and Hadits. The subjects consisted of 7 people (4 people of the debtor and the third person of the creditor).Â The results of this study show that, the background of the debts is because Profession mostly rubber farmers whose income does not settle in less favorable circumstances did not quite meet other needs caused owes the motive for the sudden need (Purposes of transportation schoolchildren and venture capital).It thus is reasonable and permissible. Then the transaction occurred at home lenders to comply with the terms and the applicable rules of the creditors, the form of contract is Qardhul hasan. Disputes which amounted to 2 people can finally be resolved by way of principled deliberation kinship known as its unique Indigenous community badamai banjar previously occurred despite the ongoing conflict between the parties promise (contract).